Chronic Ulcer Mimicking Oral Squamous Cell Carcinoma (A Case Report) - Fitria Mailiza; Rifani Rifani (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2019)
Introduction: Chronic ulcers are considered as the most common ulcerations and can be differentiated with oral squamous cell carcinoma (OSCC) by the presentation of its features. OSCC define as a malignant epithelial neoplasm and the most common neoplasm of the oral cavity. OSCC appears as a mixed white or reddish proliferative growth-like lesion from chronic trauma. Case and management: A 50 years old female came with a painful non-healing ulcer on the lateral right side of the tongue which had been exist since 6 months prior. There had been a gradual increase in the size of the ulcer over the past 6 months. The patient did not have any sistemic disease or bad habits such as chewing or smoking and did not consume alcohol either. Based on the examination, the right submandibular lymphnodes were palpable, tender, firmed and mobile.  And there was also a single oval-shaped ulcer with irregular border on the lateral aspect of the tongue in parallel with fractured and decayed lower first molar. The ulcer size was 2x1 cm in diameter, with the base covered by yellowish pseudomembran slough with indurated border. The grinding of the sharp cusp of the tooth was done, followed by the prescription of multivitamins, antibacterial mouthwash and topical corticosteroid. She was also referred to have routine blood test done. She came for the second visit after 14 days, showing improvement of the ulcer. The blood test showed no abnormal values. Discussion: Based on clinical features, the presented lesion was mimicking OSCC. According to the patient’s history taking, clinical examination and appropriate investigation, the patient was diagnosed with traumatic ulcer. Ulcer resolves and heals on the removal of causative factors. Conclusion: Chronic ulcer is one of the most common solitary ulcer presenting in the oral cavity that mimicking OSCC by the presentation of its features. In this reported case, the ulcer arises due to its constant contact with lateral right of the tongue Improvement during the treatment by eliminating suspected risk factors can ruled out the possibility of OSCC thus prevent the unnecessary treatment.